Identification of transformation-specific proteins synthesized in cryptovirogenic mammalian cells - Grófová, M; Bízik, J; Blahová, S; Geryk, J; Svoboda, J (Folia biologica, 1985)
The cryptovirogenic PR-RSH-19 (H-19) hamster cell line, derived originally from a tumour induced by the virus rescued from XC cells by transfection, was studied. The pp60v-src protein was detected by immunoprecipitation with sera from tumour-bearing rabbits (TBR sera) from lysates of H-19 cells. A closely related protein p60 was precipitated by antiserum obtained from hamsters with tumours induced by H-19 cells. The pp60v-src of H-19 cells possesses an associated kinase activity. These results are consistent with the notion that the detected pp60v-src protein is a product of the cryptic sequences in H-19 cells.
Keywords: nádorové proteiny; onkogenní protein pp60(v-src); virová transformace buněk; Cell Line; Mesocricetus; virové proteiny; proteinkinasy; křeček rodu Mesocricetus; protilátky nádorové; Antibodies, Neoplasm; viry ptačího sarkomu; Cell Transformation, Viral; králíci; Viral Proteins; Avian Sarcoma Viruses; Cricetinae; Oncogene Protein pp60(v-src); Protein Kinases; Animals; kuřecí embryo; zvířata; Sarcoma, Experimental; Rabbits; Neoplasm Proteins; buněčné linie; experimentální sarkom; Chick Embryo; křečci praví